Relasi Agama dan Negara dalam Gerakan Keagamaan Baru: Studi Kasus Komunitas Here Krisna Yogyakarta - Budi Nurhamidin; Arifin Kusuma Wardani (Tamaddun, 2019)
This study aims to see and analyze the relationship between religion and the state towards the Here Krisna sect as a spiritual movement found in Hinduism. This research uses a qualitative method with a case study approach. The problem in this study is whether there is a religious politics that occurs in Hinduism and how the relationship between religion and the state. In this regard, the points that will be elaborated by researchers include the background of the emergence of Here Krishna, the teachings conveyed, the vision of transformation, religious politics, and the relationship between religion and the state. The research results obtained that the emergence of the Here Krina stream does not become a problem for the PHDI because its existence does not make people uneasy about Hindus in general, as well as the relationship between religion and state philosophically the first precepts that read the Almighty God is based as a philosophical basis for national life and state. From the results of this study it can be understood that the Here Krisna stream can exist because it is based on Hinduism, which is an official religion and its social norms do not interfere with social life and its teachings do not conflict with the ideology of the nation as the basis of the state.